2019
DOI: 10.1021/acsomega.9b01228
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Tranilast for Potential Neuropathic Pain Treatment by Inhibition of Sepiapterin Reductase in the BH4 Pathway

Abstract: Tetrahydrobiopterin (BH 4 ) is a cofactor in the production of various signaling molecules including nitric oxide, dopamine, adrenaline, and noradrenaline. BH 4 levels are critical for processes associated with cardiovascular function, inflammation, mood, pain, and neurotransmission. Increasing pieces of evidence suggest that BH 4 is upregulated in chronic pain. Sepiapterin reductase (SPR) catalyzes both the reversible reduction of sepiapteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…We also demonstrated that SPRi reduced pain scores in mice submitted to a colitis experimental model, and that this effect was in part due to the absolute requirement of T cells for BH4 in order to expand and infiltrate tissues ( Cronin et al, 2018 ). Another FDA-approved drug, Tranilast – an anti-allergic agent, was also demonstrated to inhibit SPR in protein- and cell-based assays ( Moore et al, 2019 ) and to reduce pelvic pain caused by endometriosis in a clinical study ( Honda et al, 2013 ).…”
Section: Bh4 and Chronic Painmentioning
confidence: 99%
“…We also demonstrated that SPRi reduced pain scores in mice submitted to a colitis experimental model, and that this effect was in part due to the absolute requirement of T cells for BH4 in order to expand and infiltrate tissues ( Cronin et al, 2018 ). Another FDA-approved drug, Tranilast – an anti-allergic agent, was also demonstrated to inhibit SPR in protein- and cell-based assays ( Moore et al, 2019 ) and to reduce pelvic pain caused by endometriosis in a clinical study ( Honda et al, 2013 ).…”
Section: Bh4 and Chronic Painmentioning
confidence: 99%
“…Other SPR inhibitors discovered include 109 , 110 , QM385 ( 111 ), and tranilast ( 112 ) licensed for use in bronchial asthma (Figure ). Sulfasalazine, an FDA approved anti-inflammatory drug, was found to inhibit SPR activity through its metabolite sulfapyridine ( 113 ), which aided the discovery of some of the above-mentioned compounds (Figure ). Reducing BH4 levels by inhibiting SPR activity is a viable approach for alleviating neuropathic and inflammatory pain hypersensitivity.…”
Section: Approaches To Develop Safer Ligands For New Pain Targetsmentioning
confidence: 99%
“…The dissociation rate constant (K d ) demonstrated the dissociate rate. The equilibrium dissociation constant (K D ) demonstrated the degree of dissociation of the compounds and the 50S ribosome in the equilibrium state [30]. A low K D value indicated that the binding affinity between the compound and the 50S ribosome was strong [31].…”
Section: Spr Measurementsmentioning
confidence: 99%